Peningkatan Pengetahuan Gizi Ibu Balita Stunting dengan Metode Edukasi melalui Konseling dan Buku Resep Pangan Lokal - Resmiati Resmiati; Alvina Rasheeda Basri; Resti Resti; Aqila Maharani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
One of the nutritional problems faced today is stunting, a condition in which a child's growth is restricted due to a lack of adequate dietary intake. Providing nutrition education to mothers of toddlers with stunted children is crucial in overcoming this problem. This activity aims to increase mothers' nutritional knowledge of toddlers with stunted children in Nanggalo District, Padang City. The method used education through counselling and local food recipe books. The target group of this activity was 22 mothers of stunted toddlers. The results of this activity were effective in enhancing mothers' understanding and awareness of the importance of balanced nutrition for children. These results can be seen from the answers given by stunted toddler mothers, who initially did not know but became aware, with correct answers reaching 90% after the counselling sessions. The counselling methods allow mothers to understand more deeply the concept of nutrition and the nutritional needs of children. Food recipe books are a source of information that mothers can access again at home, providing practical guidance in choosing and preparing healthy foods quickly and affordably. With a holistic approach through counselling and food recipe books, it is hoped that mothers with toddlers can have better nutrition knowledge, implement changes in family eating patterns, and ultimately help overcome the problem of stunting in their children.